2019
DOI: 10.1002/slct.201902866
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on the Mechanisms and Pathways of the Atmospheric NH2 + BrO Reaction

Abstract: The NH2 radical reaction with BrO was characterized by combining the second‐order Møller–Plesset perturbation theory (MP2) with a 6–311++G(d,p) basis set, followed by kinetic analyses using the Rice–Ramsperger–Kassel–Marcus (RRKM) theory and transition‐state (TST) theory to forecast the product distribution and thermal rate coefficients. Addition/elimination and H‐abstraction mechanisms are observed, and three products are identified: P1 (HBr + HNO), P2 (NBr + H2O) and P3 (3NH + HOBr). At atmospheric pressure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Both modelling 25 and experimental 26,27 studies are performed to elucidate, for instance, the role of IO in the tropospheric oxidation of iodine-containing species. These works allowed us to determine the structural, energetic and thermodynamic properties of the reactive and/or non-reactive collisions between IO and the following compounds: Ar, 28 ClO, 29 BrO, 29 CF 3 O, 30 NH 2 , 31 CO, 32,33 H 2 O, 34 IO, 34 OIO, 34 HNO 3 , 35 NO, 36 O 3 , 37 NO 3 , 38 and HO 2 . 39 In particular, they showed that the first steps of such possesses correspond to the formation of weakly bound complexes between IO and these molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Both modelling 25 and experimental 26,27 studies are performed to elucidate, for instance, the role of IO in the tropospheric oxidation of iodine-containing species. These works allowed us to determine the structural, energetic and thermodynamic properties of the reactive and/or non-reactive collisions between IO and the following compounds: Ar, 28 ClO, 29 BrO, 29 CF 3 O, 30 NH 2 , 31 CO, 32,33 H 2 O, 34 IO, 34 OIO, 34 HNO 3 , 35 NO, 36 O 3 , 37 NO 3 , 38 and HO 2 . 39 In particular, they showed that the first steps of such possesses correspond to the formation of weakly bound complexes between IO and these molecules.…”
Section: Introductionmentioning
confidence: 99%